Importance of forest landscape quality for companies operating in nature tourism areas. (August 2021) - Mäntymaa, Erkki; Tyrväinen, Liisa; Juutinen, Artti; Kurttila, Mikko
Highlights: The study analyses the importance of landscape for nature-based tourism business. Nature-based tourism companies (NBTs) and general service companies are compared. Firms assess that their business increases due to the forest quality improvement. Landscape beauty is more important for the NBTs than for the other companies. The interest of companies in participating in PES mechanisms is relatively low. Abstract: To promote the growth of nature based tourism in privately owned forest areas, new policy instruments, e.g . Payments for Ecosystem Services, are needed. They could engage private forest owners and nature-based tourism companies to cooperate and support the growth of the sector. We studied the entrepreneurs' attitudes towards the importance of environmental amenities and assessments of possible improvements in forest landscapes for their business in the framework of proposed Payments for Ecosystem Services mechanism, called Landscape and Recreation Value Trade. In the analyses, we compared the assessments of two groups of companies: core nature-based tourism companies that produce most services for tourists, and general service companies that produce services for both tourists and local people. We collected a data set from an online survey that was sent to representatives of the companies of the Ruka-Kuusamo region, Finland. Core nature-based tourism companies see forest landscape beauty as being more important for their business than do general service companies. In addition, we hypothesized in the questionnaire that the quality of landscape would improve so that the impacts of forest management practices, such as the traces of clear cuttings and intensive site preparation would be less visible in future than today. If the quality improves in the core area of tourism, the activity of the business of the 2 company groups will increase equally. If, however, the quality improves in a wider area, both the number of clients and revenues will increase more for nature-based tourism companies than for general service companies. Finally, related to the implementation of suggested Payments for Ecosystem Services, nature-based tourism companies had both more interest in collecting payments from tourists for a fund for landscape quality improvement and to make a private agreement with forest owners for improving landscape quality. For the policy makers of regions where nature tourism has potential, the following suggestions are given: As attractive landscape is identified as being an important factor for the nature-based tourism business, new types of mechanisms are needed to secure a good quality of this basic resource and the positive development of this sector. As the level of interest in participating in funding and agreements related to Payments for Ecosystem Services can be rather low among entrepreneurs, an incentive mechanism for companies should also be launched. In addition, a collaborative deliberation and communication process is needed for implementing the mechanism.